Media Video Profile Sebagai Media Promosi Dan Informasi Pada SMK Bina Am Ma’mur - Desy Apriani; Haerul Haerul; Yanuar Arif Febriana (UNIVERSITAS RAHARJA, 2016)
With the development of information technology in particular in the field of multimedia in such rapid and the longer forms of media more diverse so that educational agencies to demand a more boasts information from various media. Media information and promotions that are currently used by CMS Bina Am ' prosperous. The purpose of this research was chosen as the audio visual media media information and proper promotion, by controlling hearing and vision in the form of audio visual in order to convey messages can be understood by the public at large. Existing problems, namely the medium used by the CMS Community still Prospers Am ' in the form of print media such as banners, posters and pamplet are considered less effective and efficient to use while simultaneously promoting the institutions with the best possible audio visual media so that it is selected into a medium of information and promotion of the right, by controlling hearing and vision in the form of audio visual. Because therein lies the message delivery process or how to visualize. At the same time listening and showing the contents of the message to the recipient with information through media menunjangnya, so the design of video media profile that displays the entire scope, advantages and facilities belonging to SMK Bina Am ' prosperous, can be a solution in solving problems in media promotion and information. With this study the author makes with the title of